2014
DOI: 10.1155/2014/942027
|View full text |Cite
|
Sign up to set email alerts
|

Studying Summer Season Drought in Western Russia

Abstract: During the 2010 summer, a severe drought impacted Western Russia, including regions surrounding Moscow and Belgorod (about 700 km south of Moscow). The drought was accompanied by high temperatures. Moscow recorded 37.8°C (100°F) for the first time in over 130 years of record keeping. The record heat, high humidity, dry weather, and smoke from forest fires caused increased human mortality rates in the Moscow region during the summer. The excessive heat and humidity in Western Russia were the result of atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 15 publications
7
53
0
Order By: Relevance
“…There was little change in the Southern Hemisphere BI. In the Northern Hemisphere, the increses found here were consistent with the results of others [6], [7], [17], [25] who examined 'partial' climatologies examining only certain reigions during certain seasons. The work of [6] implied that the period 1970 -1999 showed a relative minimum in Atlatnic Region winter season blocking.…”
Section: Discussion Summary and Conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…There was little change in the Southern Hemisphere BI. In the Northern Hemisphere, the increses found here were consistent with the results of others [6], [7], [17], [25] who examined 'partial' climatologies examining only certain reigions during certain seasons. The work of [6] implied that the period 1970 -1999 showed a relative minimum in Atlatnic Region winter season blocking.…”
Section: Discussion Summary and Conclusionsupporting
confidence: 91%
“…The large increase in the occurrence and days within Pacific Region Blocking is consistent with the results of [17] who examined spring and summer blocking in this region. The work of [25] also showed a large increase in blocking for the eastern Europe and western Russia region for the spring and summer seasons as well. Only the block intensity (BI) showed a decrease over the first part of the 21st century.…”
Section: The Northern Hemispherementioning
confidence: 84%
See 1 more Smart Citation
“…Also, [1] demonstrated that atmospheric blocking occurring over the Pacific Region can have a strong influence on the character of warm season conditions over the Missouri USA region. Additionally, the work of [4][5][6] demonstrated a strong tendency for summer season conditions to depend on the direction of the El Niño and Southern Oscillation (ENSO) transition. The work of [5] demonstrated a similar transition based dependence in western Russia, and [5,6] confirmed the tendency for atmospheric blocking to influence growing season conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the work of [4][5][6] demonstrated a strong tendency for summer season conditions to depend on the direction of the El Niño and Southern Oscillation (ENSO) transition. The work of [5] demonstrated a similar transition based dependence in western Russia, and [5,6] confirmed the tendency for atmospheric blocking to influence growing season conditions. Then [3] used this information along with time series analysis of crop yields to generate tendencies for soybean and corn yields based on the transition phase of ENSO.…”
Section: Introductionmentioning
confidence: 99%